Alternative Lone‐Pair ns2‐Cation‐Based Semiconductors beyond Lead Halide Perovskites for Optoelectronic Applications. Issue 32 (31st May 2021) - Li, Tianshu; Luo, Shulin; Wang, Xinjiang; Zhang, Lijun
Abstract: Lead halide perovskites have emerged in the last decade as advantageous high‐performance optoelectronic semiconductors, and have undergone rapid development for diverse applications such as solar cells, light‐emitting diodes, and photodetectors. While material instability and lead toxicity are still major concerns hindering their commercialization, they offer promising prospects and design principles for developing promising optoelectronic materials. The distinguished optoelectronic properties of lead halide perovskites stem from the Pb 2+ cation with a lone‐pair 6s 2 electronic configuration embedded in a mixed covalent–ionic bonding lattice. Herein, we summarize alternative Pb‐free semiconductors containing lone‐pair ns 2 cations, intending to offer insights for developing potential optoelectronic materials other than lead halide perovskites. We start with the physical underpinning of how the ns 2 cations within the material lattice allow for superior optoelectronic properties. We then review the emerging Pb‐free semiconductors containing ns 2 cations in terms of structural dimensionality, which is crucial for optoelectronic performance. For each category of materials, the research progresses on crystal structures, electronic/optical properties, device applications, and recent efforts for performance enhancements are overviewed. Finally, the issues hindering the further developments of studied materials are surveyed along with possible strategies to overcome them, which also provides an outlook on the future research in this field. Abstract : An overview of recent progress on emerging Pb‐free semiconductors containing lone‐pair ns 2 cations is provided, with the purpose of providing valid insights for discovering auspicious optoelectronic materials other than lead halide perovskites. The issues hindering performance enhancement and the design strategies of novel ns 2 ‐cation‐based optoelectronic semiconductors are discussed.